2016
DOI: 10.1021/jacs.6b04082
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Relative Configuration from Residual Chemical Shift Anisotropy

Abstract: Determination of relative configuration is frequently a rate-limiting step in the characterization of small organic molecules. Solution NMR-based nuclear Overhauser effect and scalar J-coupling constants can provide useful spatial information but often fail when stereocenters are separated by more than 4-5 Å. Residual dipolar couplings (RDCs) can provide a means of assigning relative configuration without limits of distance between stereocenters. However, sensitivity limits their application. Chemical shift is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
151
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(155 citation statements)
references
References 52 publications
3
151
0
1
Order By: Relevance
“…The scaling parameter for this procedure can be optimized along with the alignment tensor during the SVD fitting procedure, simplifying and unbiasing the use of the protocol while still retaining the capability to discriminate relative configuration. As became obvious with the example of 10‐epi‐8‐deoxycumambrin B, the assumption for the isotropic correction introduced in Nath and coworker's study is shown to be wrong due to anisotropic distribution of CSA tensors in the molecule. This prevented the determination of the correct configuration.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The scaling parameter for this procedure can be optimized along with the alignment tensor during the SVD fitting procedure, simplifying and unbiasing the use of the protocol while still retaining the capability to discriminate relative configuration. As became obvious with the example of 10‐epi‐8‐deoxycumambrin B, the assumption for the isotropic correction introduced in Nath and coworker's study is shown to be wrong due to anisotropic distribution of CSA tensors in the molecule. This prevented the determination of the correct configuration.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent collaborative work, some of us, with other collaborators, presented two robust approaches to measure RCSAs based on the use of polymethylmethacrylate (PMMA) gels . The first one was based on a device developed by Liu and Prestegard that uses a tube with two parts of different diameter that is open at both ends.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the possibility to perform NMR experiments in anisotropic media allows the exploration of interesting interactions, such as residual dipolar couplings (RDCs) and residual chemical shift anisotropy (RCSAs), which can be highly valuable for structural determination purposes. 5 The use of computerassisted structural elucidation (CASE) programs has been significantly helpful to handle information provided by different NMR experiments and transform it into a plausible 2D, or even 3D, structure. 6 All in all, NMR spectroscopy has advanced to such a stage that nowadays we can routinely run NMR experiments that would have been unthinkable some years ago.…”
Section: Introductionmentioning
confidence: 99%